110 Improving Asthma Education in the Emergency Department: A Quality Improvement Initiative. (19th August 2020) - Wohlleben, Mikayla; Meleady, Laura; Oei, Krista; Seaton, Claire
Abstract: Introduction/Background: Asthma education and action plans have been shown to improve compliance and symptom control. Provincial guidelines, created in 2015, included asthma action plans, but use of these resources across our site was not consistent. Objectives: The objectives of this study were to develop and implement an asthma education package, standardize discharge instructions and improve appropriate referrals to Asthma Clinics. Design/Methods: Using process mapping, staff surveys and patient interviews, we undertook a current state analysis. The resulting change ideas were implemented between October 2018 and January 2020 in 5 PDSA (Plan Do Study Act) cycles, utilizing chart reviews and a standardized data tool to measure outcomes. Rates of repeat Emergency Department (ED) attendances, 2 weeks following the initial encounter and overall rates of ED asthma visits were assessed, using patient medical record data. PDSA 1: Action Plan implementation and ED training PDSA 2: Community Pediatric Physicians Directory and pre-printed Discharge and Prescription Form PDSA 3: Repeat ED training PDSA 4: Production and implementation of Video - Childhood Asthma: A Guide for Families and Caregivers (https://bit.ly/pediatric-asthma-video ) PDSA 5: Asthma Discharge Checklist Results: Two-hundred-and-twenty-five ED presentations were reviewed, 65.2% (146/224) had a previous diagnosis of asthma. 48.9% (110/225) reported using an inhaled corticosteroid (ICS) at presentation. 89.7% (201/224) had not seen a healthcare provider during this acute illness. Asthma action plan utilization increased from 0% at baseline to an average of 60%, sustained over 2 years. 74.2% (167/225) had an ICS prescribed or advised at discharge. Only 3.8% (8/209) of patients re-presented to an ED within 2 weeks of this asthma visit. 57.3% (129/225) children were referred for ongoing pediatric care: either by a community pediatrician (72.9%; 94/129) or our hospital Asthma Clinic (34.8%; 32/129). Between 2017 and 2019, there was no significant change in total asthma presentations to our ED/per year (1300, 1395 and 1307, respectively) (Figure 1 ). Conclusion: A standardized asthma education package including pre-printed discharge resources, asthma action plans, and a provincially adopted, multi-language education video was successfully implemented into our ED. This demonstrates a multi-disciplinary approach to asthma education that can be utilized across the province. Our data highlights the need for a strong community-based approach for asthma care, and further work is ongoing to assess the efficacy of this education package on medication compliance and recurrent ED visits.